2018
DOI: 10.1016/j.ijsu.2018.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for surgical site infection following operative treatment of ankle fractures: A systematic review and meta-analysis

Abstract: Patients involved with the above-mentioned medical conditions were at risk for surgical site infection after open reduction and internal fixation of ankle fracture. The present study may in this respect serve as a baseline reference and this knowledge will allow the formulation of public health strategies to prevent surgical site infection after orthopedic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 35 publications
5
61
0
1
Order By: Relevance
“…Surgery in elderly patients represents an at‐risk procedure in terms of both anaesthetic and surgical plan, and the ASA classification system was a practicable and excellent assessment tool for estimation of the inpatients' physical status and endurance capability to surgery and anaesthesia. The ASA score has been identified as an independent risk factor of postoperative SSI in orthopaedics and other disciplines . In the present study, the ASA classified III‐IV score was associated with quite a high risk of SSI (OR = 2.2).…”
Section: Discussionsupporting
confidence: 49%
“…Surgery in elderly patients represents an at‐risk procedure in terms of both anaesthetic and surgical plan, and the ASA classification system was a practicable and excellent assessment tool for estimation of the inpatients' physical status and endurance capability to surgery and anaesthesia. The ASA score has been identified as an independent risk factor of postoperative SSI in orthopaedics and other disciplines . In the present study, the ASA classified III‐IV score was associated with quite a high risk of SSI (OR = 2.2).…”
Section: Discussionsupporting
confidence: 49%
“…The gender difference in risk of infection issues has been little consistent across orthopaedic studies, and almost all the studies specified at ankle fractures did not identify the independent association with postoperative SSI 2,7,16,18,22,23 . In this study, we found the 2.69‐fold increased risk of SSI in men.…”
Section: Discussionmentioning
confidence: 48%
“…Meng et al 7 reported the incidence rate of deep SSI was 2.83% in 2617 patients with ankle fracture treated by open reduction and internal fixation (ORIF). Shao et al 18 pooled the data in a meta‐analysis of 8103 ankle fractures by ORIF and found the overall rate of SSI was 7.2%. In contrast, this study included ankle fractures reduced by either open or closed manner, and reported a comparable incidence of 2.9%.…”
Section: Discussionmentioning
confidence: 99%
“…Often, early hospitalization was associated with the need for additional consultations or examinations. Nevertheless, the duration of stay of patients in the ward before the surgery directly correlates with the risk of infectious complications in the postoperative period, and therefore, admission to the hospital on the eve of the operation should be considered optimal [10].…”
Section: Resultsmentioning
confidence: 99%